A contribuição da anáfora encapsuladora para a organização da informação em dissertações produzidas por alunos do 3º ano do ensino médio de Santarém - CORDEIRO, Maria Audirene de Souza (Universidade Federal do Pará, 2018)
This work shows presents the result of an investigation about the encapsulating anaphora contribution for the organization of information in dissertations. For this research, it was used 60 (sixty) texts produced by students from 3rd (third) grade of High School from Dom Amando School. The theoretical basis founds on Koch’s (1997, 2001, 2004, 2005), Val’s (1999, 2003), Marcuschi’s (2001, 2002), Ilari’s (1992, 2001, 2005) Cavalcante’s (2001, 2003), Sousa’s(2003), Mondada’s ( 2003), Apothéloz’s (2003), Apothéloz and Chanet’s (2003), Conte’s (2003) and Francis (2003). The analysis of the texts points out that, in spite of encapsulating anaphora being an important referenciation strategy to guarantee the remission and summarization of preceding textual portions, it was used in 15 (fifteen) of the 60 (sixty) dissertations that composes the corpus. In these texts I recognize the formal contexts where encapsulating anaphora were used, I analyse how they contribute for the organization of argumentative sequences that compose the dissertation and how the inadequate use of this strategy can damage the rgumentative process. The results point out that the encapsulating anaphora is really a fundamental strategy for the organization of argumentative sequences, because summarizing preceding textual portions, this particular kind of anaphora allows the text producer to: a) work with different arguments and relat them to each other with no repeating sequences that were mentioned; b) conduct the argumentative line in order that the reader is convinced of the points of view effectiveness defended in text and c) show changes in argumentative sequence, indicating that the author’s text is getting through from an argumentative point to another one. Besides that, depending on the chosen noun to compose the encapsulating anaphora, we can realize how the producer evaluates and wants the reader interpret preceding sequences encapsulating anaphora. In Portuguese Language classes and/or production of text classes, attention should be given to the fuction of encapsulating anaphora because this strategy allows the construction of argumentative logical sequences and makes possible the text producer to organize his/her texts in a much more productive way the argumentative process in dissertations.